Faecalibacterium prausnitzii regulates carbohydrate metabolic functions of the gut microbiome in C57BL/6 mice - Peiling Geng; Ni Zhao; Yufan Zhou; Reuben S. Harris; Yong Ge (Gut Microbes)
The probiotic impact of microbes on host metabolism and health depends on both host genetics and bacterial genomic variation. Faecalibacterium prausnitzii is the predominant human gut commensal emerging as a next-generation probiotic. Although this bacterium exhibits substantial intraspecies diversity, it is unclear whether genetically distinct F. prausnitzii strains might lead to functional differences in the gut microbiome. Here, we isolated and characterized a novel F. prausnitzii strain (UT1) that belongs to the most prevalent but underappreciated phylogenetic clade in the global human population. Genome analysis showed that this butyrate-producing isolate carries multiple putative mobile genetic elements, a clade-specific defense system, and a range of carbohydrate catabolic enzymes. Multiomic approaches were used to profile the impact of UT1 on the gut microbiome and associated metabolic activity of C57BL/6 mice at homeostasis. Both 16S rRNA and metagenomic sequencing demonstrated that oral administration of UT1 resulted in profound microbial compositional changes including a significant enrichment of Lactobacillus, Bifidobacterium, and Turicibacter. Functional profiling of the fecal metagenomes revealed a markedly higher abundance of carbohydrate-active enzymes (CAZymes) in UT1-gavaged mice. Accordingly, UT1-conditioned microbiota possessed the elevated capability of utilizing starch in vitro and exhibited a lower availability of microbiota-accessible carbohydrates in the gut. Further analysis uncovered a functional network wherein UT1 reduced the abundance of mucin-degrading CAZymes and microbes, which correlated with a concomitant reduction of fecal mucin glycans. Collectively, our results reveal a crucial role of UT1 in facilitating the carbohydrate metabolism of the gut microbiome and expand our understanding of the genetic and phenotypic diversity of F. prausnitzii.